Distribution and identification of sand flies naturally infected with Leishmania from the Southeastern Peruvian Amazon. - Victor Zorrilla; Maxy B De Los Santos; Liz Espada; Rocío Del Pilar Santos; Roberto Fernandez; Albino Urquia; Craig A Stoops; Sarah-Blythe Ballard; Andres G Lescano; Gissella M Vásquez; Hugo O Valdivia (PLoS Neglected Tropical Diseases, 2017)
Cutaneous leishmaniasis (CL) is an important health problem in the New World affecting civilian and military populations that are frequently exposed in endemic settings. The Peruvian region of Madre de Dios located near the border with Brazil is one of the most endemic CL regions in South America with more than 4,451 reported cases between 2010 and 2015 according to the Peruvian epidemiology directorate. However, little is known regarding the diversity and distribution of sand fly vectors in this region. In this study, we aimed to characterize the sand fly fauna in this endemic setting and identify sand fly species naturally infected with Leishmania possibly involved in pathogen transmission.Sand fly collections were carried out during 2014 and 2015 in the communities of Flor de Acre, Villa Primavera, Mavila and Arca Pacahuara using CDC light traps and Shannon traps. Collected specimens were identified and non-blood-fed females were selected for Leishmania infection screening using kinetoplastid DNA-PCR (kDNA-PCR) and nested Real time PCR for species identification.A total of 10,897 phlebotomines belonging to the genus Lutzomyia (58 species) and Brumptomyia (2 species) were collected. Our study confirmed the widespread distribution and abundance of Lutzomyia (Trichophoromyia) spp. (24%), Lu. whitmani (19.4%) and Lu. yucumensis (15.8%) in the region. Analysis of Shannon diversity index indicates variability in sand fly composition across sites with Villa Primavera presenting the highest sand fly diversity and abundance. Leishmania screening by kDNA-PCR resulted in 45 positive pools collected from Flor de Acre (34 pools), Mavila (10 pools) and Arca Pacahuara (1 pool) and included 14 species: Lu. yucumensis, Lu. aragoi, Lu. sallesi, Lu. sherlocki, Lu. shawi, Lu. walkeri, Lu nevesi, Lu. migonei, Lu. davisi, Lu. carrerai, Lu. hirsuta, Lu. (Trichophoromyia) spp., Lu. llanosmartinsi and Lu. whitmani. Lutzomyia sherlocki, Lu. walkeri and Lu. llanosmartinsi had the highest infection rates (8%, 7% and 6%, respectively). We identified Leishmania guyanensis in two Lu. whitmani pools, and L. braziliensis in two Lu. llanosmartinsi pools and one Lu. davisi pool.Based on our collections there is high sand fly diversity in Madre de Dios, with differences in sand fly abundance and species composition across sites. We identified 14 sand fly species naturally infected with Leishmania spp., having detected natural infection with L. (V.) guyanensis and L. (V.) braziliensis in three sand fly species. These results suggest the presence of several potential vectors that vary in their spatial and geographical distribution, which could explain the high prevalence of CL cases in this region.